The Ordering of Portfolios in Terms of Mean and Variance - Chipman, John S. (Review of Economic Studies, 1973)
Journal Article The Ordering of Portfolios in Terms of Mean and Variance Get access John S. Chipman John S. Chipman University of Minnesota Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 2, April 1973, Pages 167–190, https://doi.org/10.2307/2296646 Published: 01 April 1973